GAMBARAN TINGKAT KECEMASAN PERSIAPAN OPERASI SECTIO CAESARIA PADA IBU HAMIL - Muhammad Syakir Marzuki; Mohammad Hendro Mustaqim (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Sectio Caesarea (SC) is a medical procedure that is needed to assist labor with certain indications, either due to maternal health problems or fetal conditions.The incidence of Sectio Caesarea (SC) surgery at the Mother and Child Hospital is approximately 15 cases each month. Based on data in the hospital, the total number of patients who performed Sectio Caesarea (SC) in January to December 2019 was as many as 625 patients. Anxiety will have a negative impact on the mother sectio caesarae because of the side effects caused when the mother has finished surgery, namely an increase in blood pressure and pulse which will result in uterine contractions that are less than the maximum, causing bleeding. The purpose of this study was to describe the level of anxiety in preparation for caesarean section surgery in pregnant women. This research is a research using the method of literature study or literature review. The review literature is a comprehensive overview of the research that has been done on a specific topic to show the reader what is already known about the topic and what is not yet known, to look rationally from the research that has been done or for further research ideas. The method of literature study is a series of activities relating to the method of collecting library data, reading and recording, and managing writing material. From the results of the literature review study on the description of anxiety levels of sectio caesarean preparation in pregnant women it was found that there was an influence of age, parity, knowledge and family support for anxiety. It is expected that educational institutions will provide knowledge about the anxiety level of preparing caesarean section surgery in pregnant women. In addition, educational institutions also provide knowledge about the nursing community so that students can provide good intervention to the community in dealing with cesarean section surgery.Keywords: Anxiety Level, Sectio Caesarea, Pregnant Women